Sintesis Komposit Fe3O4/Hidroksiapatit Menggunakan Metode Presipitasi Dengan Variasi Rasio Ca/P Dan Kecepatan Pengadukan - Adha Widoni; Ahmad Fadli; Komalasari Komalasari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Fe3O4/Hydroxyapatite composite can be applied in the biomedical field especially for drug delivery systems. The purpose of this research was to determine the effect of Ca/P ratio and stirring rate for the composite magnetite/hydroxyapatite characteristic. Synthesis of Fe3O4/Hydroxyapatite composites using the precipitation method. Variation of Ca/P ratio 0.67; 1.67; 2.67 and stirring rate of 400 rpm, 600 rpm, 800 rpm. 20.35 mmol (NH4)2HPO4 solution with 150 ml was added to mixed the magnetite suspension and 34 mmol Ca(NO3)2.4H2O solution. NH4OH was added to the solution until pH 11 and then, the suspension was aged for one day. The magnetic suspension was washed with distillate water until pH neutral. The precipitate was dried and sintered at temperature 400˚C until composite powder obtained. Composite powder was characterized by X-ray diffraction (XRD), and vibrating sample magnetometer (VSM). Increasing of Ca/P ratio from 0.67 to 1.67 increased the crystal size and crystallinity of the composite, then decreased the size of the crystal and crystallinity at the Ca/P ratio 2.67. Crystallinity is obtained at 75.47% - 81.77%. While the effect of stirring rate from 400 rpm to 600 rpm increased the crystal size from 20.75 nm to 25.23 nm, Then, decreased at stirring rate of 800 rpm by 21.68 nm. Fe3O4/Hydroxyapatite composite were superparamagnetic with saturation magnetization (Ms) 11.97 emu/gr. Keywords: Drug Delivery, Hydroxyapatite, Magnetite, Magnetic Properties